iMOOC on Climate Change: Evaluation of a Massive Open Online Learning Pilot Experience - Coelho, José; Teixeira, António; Nicolau, Paula Bacelar; Caeiro, Sandra; Rocio, Vitor (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2015)
MOOCs are a recent phenomenon, although given their impact, they have been subject to a large debate. Several questions have been raised by researchers and educators alike regarding their sustainability, both economically and as an efficient mode of education provision. In this paper we contribute to this discussion by presenting a case study of the MOOC on Lived Experiences of Climate Change, which piloted the iMOOC pedagogical model developed at Universidade Aberta (UAb), the Portugese Distance Learning University. The iMOOC is a hybrid model which incorporates elements from existing MOOCs but adds other features drawn from UAb's experience with online learning and aims at better integrating in the larger context of the institutional pedagogical culture. The iMOOC implied also an integration of platforms - Moodle and Elgg. The pilot course had more than one thousand registrations, and it was the largest MOOC course on Portuguese language delivered so far. We discuss the effort required to design and deliver the course, the technological solution developed, and the results obtained. We registered a moderate effort to create and run the course, ensured by internal staff from the University. The technological solution was a success: an integrated architecture combining well-established, well-tested open software. The completion rate was 3.3%, but the high success of this innovative learning experience was demonstrated by the active involvement of about 50% of the registered participants, that followed the course until the end. Lessons learned from this experience and future research on the field are also discussed.